Retinal detachments in a patient with minimal change nephrotic syndrome: Case report and review of the literature - Ye, Chunjian; Qiu, Miaohua; Zhong, Yu; Chen, Jiejian (Frontiers in Nephrology, 2023)
Background To report an unusual case of minimal change nephrotic syndrome with sudden bilateral retinal detachment. Case presentation A 54-year-old woman with minimal change nephrotic syndrome presented with sudden-onset visual blurring in both eyes. Optical coherence tomography scans revealed macular schisis and extramacular intraretinal separation. A kidney biopsy confirmed the diagnosis of minimal change disease. Glucocorticoid therapy was quickly started. During remission, her vision was restored, with complete resolution of the subretinal fluid observed on optical coherence tomography. Conclusions In minimal change nephrotic syndrome, fluid accumulation in the retina layer may occur, and gravity-induced vitreous traction on the inferior retina may cause retinal detachment. Patients should be advised to avoid large swings of the head and neck, handstands, and other activities that may increase the risk of retinal detachment. The possibility of retinal detachment should be considered when blurred vision occurs.